Focal lymphoid aggregates (nodules) in bone marrow biopsies: differentiation between benign hyperplasia and malignant lymphoma--a practical guideline. - Thiele, J (1999)
AIMS: To provide practical guidelines for the differentiation between benign and malignant focal lymphoid aggregates (lymphoid nodules) in routinely referred bone marrow trephine biopsies, using a synoptic approach including clinical data and histological workup. METHODS: For easy identification of very small lymphoid infiltrates the chloroacetate esterase stain was applied as a screening procedure. This allowed the identification of 491 formalin fixed, paraffin wax embedded specimens with one or more lymphoid nodules. Examination of lymphoid infiltrates included such variables as histotopography, demarcation, cytology, reticulin fibres, and immunohistochemistry with a set of monoclonal antibodies (CD20, CD45R, CD45R0, CD3, CD43). Evaluation of clinical and morphological data was carried out independently. In case of malignant lymphomas, a correlation with corresponding lymph node findings was made. RESULTS: 352 patients had benign focal lymphoid aggregates usually associated with systemic autoimmune diseases, chronic myeloproliferative disorders, toxic myelopathy, and viral infections. Discrete nodular infiltrates of (small cell) malignant lymphomas (n = 93) simulating benign hyperplasia were found in chronic lymphocytic leukaemia, germinal centre cell lymphomas (CB-CC), and lymphoplasmacytic/cytoid lymphomas (LPI). In addition to immunoreactivity, certain histological variables proved distinctive. These were: (1) histotopography, that is, localisation of the lymphoid aggregates within the bone marrow space; (2) relation to the surrounding tissue: margination or interstitial spillage of lymphoid cells; and (3) increase in reticulin fibres. CONCLUSIONS: A combined diagnostic procedure identifying several distinctive features, in particular histotopography and immunohistochemistry, provides a most promising way of discriminating reactive from neoplastic lymphoid nodules in the bone marrow.